2014
DOI: 10.2298/bah1403433p
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between the swine infectious diseases agents and low levels of mycotoxins in swine feed

Abstract: The aim of the paper was to evaluate the possible interaction between the presence of swine infectious diseases and low levels of mycotoxins in swine feed. The material for this research included the samples from three swine farms, where health disorders in different swine categories were detected. The applied research methods included: epidemiological and clinical evaluation, pathological examination, bacteriological and virological laboratory testing and microbiological feed testing, in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In gilts exposed to various doses of ZEN over a period of 4 weeks, the mycotoxin caused mucosal inflammations as well as damage to the epithelium and mucosa, which is consistent with the results documenting ZEN’s negative influence on intestinal defense [ 42 ]. The results of in vivo studies demonstrated that both low and high doses of ZEN could contribute to intestinal inflammations [ 148 ] and allergies [ 49 ].…”
Section: Activity Of Zenmentioning
confidence: 99%
“…In gilts exposed to various doses of ZEN over a period of 4 weeks, the mycotoxin caused mucosal inflammations as well as damage to the epithelium and mucosa, which is consistent with the results documenting ZEN’s negative influence on intestinal defense [ 42 ]. The results of in vivo studies demonstrated that both low and high doses of ZEN could contribute to intestinal inflammations [ 148 ] and allergies [ 49 ].…”
Section: Activity Of Zenmentioning
confidence: 99%
“…Asymptomatic carriers of the bacterium, either those having survived the acute form of the disease or those that were subclinically infected, are an important source of infection. The severity of disease can be signifi cantly infl uenced by differences in virulence potential of different isolates and stress factors, different co-infections with other pathogens, and extrinsic factors such as poor husbandry and insuffi cient biosecurity [28,31,35,49].…”
Section: Actinobacillus Pleuropneumoniae (App)mentioning
confidence: 99%
“…It needs to be stressed that latently infected pigs can be a permanent source of reinfection in a herd. The latent infection may be reactivated by stress (transport, mixing of pigs) or due to swine feed contamination with different mycotoxins [28,31].…”
Section: Aujeszky's Disease -Pseudorabies (Ad)mentioning
confidence: 99%
See 1 more Smart Citation
“…A major problem associated with animal feed contaminated with mycotoxins is not acute disease, but rather the ingestion of low levels of toxins, which may cause an array of metabolic, physiologic and immunologic disturbances (Pro danov-Radulović et al 2014;Waśkiewicz et al 2014). Consumption of fungal toxins in swine as a species may decrease resistance to infectious diseases (Prodanov-Radulović et al 2011;Prodanov-Radulović et al 2014). Also, chronic exposure can lead to anorexia, reduced weight gain, as well as nutritional efficiency and neuroendocrine changes (Pestka, 2007;Prodanov-Radulović et al 2013).…”
Section: Introductionmentioning
confidence: 99%